1994
DOI: 10.1136/bmj.309.6962.1111
|View full text |Cite
|
Sign up to set email alerts
|

Population need for renal replacement therapy in Thames regions: ethnic dimension

Abstract: Black and Asian people receive and have a greater need for renal replacement therapy, and the need will increase as these populations age. These findings have important implications for the provision of renal services in districts with a high proportion of ethnic minorities and for the management of diabetes mellitus and hypertension, two important causes of end stage renal failure in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 15 publications
0
51
1
Order By: Relevance
“…13 On the other hand, the association between hypertension and renal failure, though well-known, [10][11][12] has not had a causative link established. 4,14 Circumstantial evidence to date, however, suggests that progression of renal failure can be reduced by treatment of high BP. 4 Morbidity and mortality from cardiovascular and renal disease in the community could undoubtedly be improved if facilities for the prevention and treatment of high BP were available.…”
Section: Discussionmentioning
confidence: 99%
“…13 On the other hand, the association between hypertension and renal failure, though well-known, [10][11][12] has not had a causative link established. 4,14 Circumstantial evidence to date, however, suggests that progression of renal failure can be reduced by treatment of high BP. 4 Morbidity and mortality from cardiovascular and renal disease in the community could undoubtedly be improved if facilities for the prevention and treatment of high BP were available.…”
Section: Discussionmentioning
confidence: 99%
“…We selected Muslims of Pakistani origin living in North England for comparison with white English nationals from the same locale as Muslims of Pakistani origin represent the largest sub-group of Muslims living in the UK. The views of Muslims of Pakistani origin about organ donation are chronically underresearched even though British Asians have three times the risk of the white population of suffering renal disease (Roderick, Raleigh, McGowan & Mallick, 1994). Moreover, the low number of British Asians carrying an organ donor card means that Asians often have to wait 10-12 months longer than their white counterparts for a kidney transplant due to the necessity of blood group matching (Carlisle, 1995).…”
Section: Muslims Of Pakistani Origin and White English Nationals Livimentioning
confidence: 99%
“…1 It is a particular problem in Africans and Caribbeans living in the United Kingdom 1,2 with stroke and endstage renal failure being the major causes of death and disability. [3][4][5][6] In a recent population-based survey of cardiovascular risk factors in ethnic minority groups we found that nearly 50% of middle-aged black people (both West Africans and AfroCaribbeans) had high blood pressure requiring treatment. [2][3][4][5][6][7] High blood pressure in blacks is associated with low plasma renin activity, an index of sodium retention and volume expansion, and appears to be more Correspondence: Dr GA Sagnella (Physiological Medicine) or Professor FP Cappuccio (General Practice and Primary Care), St George's Hospital Medical School, Cranmer Terrace, London SW17 0RE, UK E-mail: g.sagnellaȰsghms.ac.uk or f.cappuccioȰsghms.ac.uk Received 13 July 2000; revised and accepted 27 November 2000 ing to increasing blood pressure and presence or absence of drug therapy.…”
Section: Introductionmentioning
confidence: 99%